(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
With the help of algebraic addition of strength and substance method was calculated the pit wall stability and overburden dump for Lunevsky limestone deposit. Executed calculations are evidence of the fact that the choice of dump angle 50° is substantiated in case, if worked out areas were filled by 15 m overburden dump layer.